Social and economic characteristics of financial and blood donors in Germany - Eckhard Priller; Jürgen Schupp (DIW Economic Bulletin, 2011)
Surveys of the German Socio-Economic Panel Study (SOEP) have shown that Germans donated around 5.3 billion euros in 2009- right in the middle of the financial and economic crisis. The type and amount of donations made is well documented in Germany. However, until recently, there was very little information available on the identity of Germans who share their income with people in need. A new survey in the long-term SOEP study has now made it possible to collect this information systematically for the first time and to investigate questions such as: Which social groups do people who make donations belong to? Does a high income increase the willingness to donate money? Do education and age play a role? Do people who are happy donate more? Do the same motives apply for giving money as, for example, giving blood? In order to find answers to these questions, existing data sources on the Germans' willingness to give were analyzed, verified and matched with SOEP data for the first time. The results are conclusive: Women donate more than men, older people more than younger people. This only applies to donating money, however. As regards giving blood, social and financial differences are of much less importance. Here almost all social groups and classes donate as much-albeit much less frequently. While almost 40 percent of all Germans donated money in 2009, only seven percent gave.
Keywords: D31; D64; Z13; 330; donations; income; altruistic; SOEP